Nascent HDL (High-Density Lipoprotein) Discs Carry Cholesterol to HDL Spheres: Effects of HDL Particle Remodeling on Cholesterol Efflux - Navdaev, Alexei V. (Arterioscler Thromb Vasc Biol, 2020)
OBJECTIVE: To characterize the fate of protein and lipid in nascent HDL (high-density lipoprotein) in plasma and explore the role of interaction between nascent HDL and mature HDL in promoting ABCA1 (ATP-binding cassette transporter 1)-dependent cholesterol efflux. APPROACH AND RESULTS: Two discoidal species, nascent HDL produced by RAW264.7 cells expressing ABCA1 (LpA-I [apo AI containing particles formed by incubating ABCA1-expressing cells with apo AI]), and CSL112, human apo AI (apolipoprotein AI) reconstituted with phospholipids, were used for in vitro incubations with human plasma or purified spherical plasma HDL. Fluorescent labeling and biotinylation of HDL were employed to follow the redistribution of cholesterol and apo AI, cholesterol efflux was measured using cholesterol-loaded cells. We show that both nascent LpA-I and CSL112 can rapidly fuse with spherical HDL. Redistribution of the apo AI molecules and cholesterol after particle fusion leads to the formation of (1) enlarged, remodeled, lipid-rich HDL particles carrying lipid and apo AI from LpA-I and (2) lipid-poor apo AI particles carrying apo AI from both discs and spheres. The interaction of discs and spheres led to a greater than additive elevation of ABCA1-dependent cholesterol efflux. CONCLUSIONS: These data demonstrate that although newly formed discs are relatively poor substrates for ABCA1, they can interact with spheres to produce lipid-poor apo AI, a much better substrate for ABCA1. Because the lipid-poor apo AI generated in this interaction can itself become discoid by the action of ABCA1, cycles of cholesterol efflux and disc-sphere fusion may result in net ABCA1-dependent transfer of cholesterol from cells to HDL spheres. This process may be of particular importance in atherosclerotic plaque where cholesterol acceptors may be limiting.